Teaching consecutive interpretation by means of “Dialog Nibelung” software - Strilets, Valentyna; Kolos, Yulia (Видавництво Львівської політехніки, 2013)
The article deals with an urgent problem of computer software implementation in professional interpretation competence formation. The article is aimed at describing “Dialog Nibelung” software facilities that can contribute to interpretation skills formation and match them to the system of relevant exercises. The system of computer-mediated exercises for teaching interpretation was developed.
Keywords: translation; professional competence; consecutive interpretation; source text; target text; skill; translation shorthand; computer-mediated exercise; skills formation exercises; skills development exercises